Lab loans management system for NTU computer science labs - Lim, Corliss Zi Hwee (Nanyang Technological University, 2023)
NTU lab technicians rely on manual processes for managing equipment loans to students and staff. This manner of record keeping is space inefficient, time consuming and error prone. Lab technicians want a system that will automate this process. This project will digitize loaning of equipment and track loan records for stock keeping in NTU labs. It aims to streamline loan management and provide accurate stock keeping for lab technicians.